Adaptation of Mycobacterium tuberculosis to Impaired Host Immunity in HIV-Infected Patients. (17th August 2016) - Walter, Nicholas D.; de Jong, Bouke C.; Garcia, Benjamin J.; Dolganov, Gregory M.; Worodria, William; Byanyima, Patrick; Musisi, Emmanuel; Huang, Laurence; Chan, Edward D.; Van, Tran T.; Antonio, Martin; Ayorinde, Abigail; et al.
Abstract: Background. It is unknown whether immunosuppression influences the physiologic state of Mycobacterium tuberculosis in vivo. We evaluated the impact of host immunity by comparing M. tuberculosis and human gene transcription in sputum between human immunodeficiency virus (HIV)–infected and uninfected patients with tuberculosis. Methods. We collected sputum specimens before treatment from Gambians and Ugandans with pulmonary tuberculosis, revealed by positive results of acid-fast bacillus smears. We quantified expression of 2179 M. tuberculosis genes and 234 human immune genes via quantitative reverse transcription–polymerase chain reaction. We summarized genes from key functional categories with significantly increased or decreased expression. Results. A total of 24 of 65 patients with tuberculosis were HIV infected. M. tuberculosis DosR regulon genes were less highly expressed among HIV-infected patients with tuberculosis than among HIV-uninfected patients with tuberculosis (Gambia, P < .0001; Uganda, P = .037). In profiling of human genes from the same sputa, HIV-infected patients had 3.4-fold lower expression of IFNG ( P = .005), 4.9-fold higher expression of ARG1 ( P = .0006), and 3.4-fold higher expression of IL10 ( P = .0002) than in HIV-uninfected patients with tuberculosis. Conclusions. M. tuberculosis in HIV-infected patients had lower expression of the DosR regulon, a critical metabolic and immunomodulatory switch induced by NO, carbon monoxide, and hypoxia. Our human data suggest that decreased DosR expression may result from alternative pathway activation of macrophages, with consequent decreased NO expression and/or by poor granuloma formation with consequent decreased hypoxic stress.